IoT Based Gas Leakage Detection and Ventilation for Home Using Solar - adam, ADAM ISKANDAR BIN AZMAN (Progress in Engineering Application and Technology, 2024)
This project involves developing an IoT-based Gas Leakage Detection And Ventilation utilizing the ESP32 microcontroller with Manual Control & Monitoring System capabilities. It emphasizesthe creation of an intelligent exhaust fan setup utilizing environmental sensors like theMQ-2 Gas/Smoke Sensor and the DHT11 Humidity Temperature Sensor, to monitor factors such as gas levels, temperature, and humidity. Data collected from these sensors is transmitted to the Blynk Dashboard for real-time monitoring. A significant aspect of the project is the automation of the exhaust fan, which is connected to a 7V DC power supply via a relay. The fan’s operation is regulated based on the gas levels detected by the MQ-2 sensor. In the event of high gas levels, the system automatically activates the fan to ventilate the area, thereby enhancing safety and improving air quality. Furthermore, the system offers manual control of the fan through the Blynk Dashboard. This feature allows users to override the automated settings as needed, providing personalized control tailored to individual preferences or requirements. This IoT-based solution integrates smart monitoring and control technology for an exhaust fan, demonstrating the practical application of IoT in enhancing home and environmental safety.